DEVELOPMENT OF A SIMPLE ENGLISH BOOK TO IMPROVE VOCABULARY MASTERY FOR X-1 GRADE STUDENTS AT SMAS RAUDLATUL ULUM GONDANGLEGI - Mufidatus Solihah; Tyas Alhim Mubarok; Ahmad Saifudin (Journey: Journal of English Language and Pedagogy, 2023)
Vocabulary is an important component in English and the main supporting aspect for mastering a language. English is an international language that is often used in conversations between countries. English skills in the modern era are needed, especially in the world of work and education. After observing X-1 grade students at SMAS Raudlatul Ulum Gondanglegi, researchersfound a problem with students' lack of vocabulary skills. Therefore,researchers created learning media that can improve students’ vocabulary skills, namely The Simple English Book learning media. Researchers used development research methods with the ADDIE research model; Analysis, Design, Development, Implementation, and Evaluation. The Simple English Book learning media obtained validation results from media experts of 82.5%, meaning that the media was included in the very valid category and 60% of learning experts, which meant that the media was quite valid, and the average results of the questionnaire for all student responses to the media received 2,002.5 and from the teacher response questionnaire for the English superior program, it was obtained 77.5%, in conclusion, learning media is learning media that is interesting, easy to use and easy to understand.